Assessment of the promotional activities of Las Piñas National High School Library - Medina, Virgilio G., Jr.; Timoteo, Christine B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
Promotional activities enable many libraries to promote library services that would meet the informational needs of their respective communities. These activities must be guided by a systematic and organized plan in order to achieve effectiveness. Many studies emphasize that money or budget constraints should not be considered as a hindrance when promoting library services and collections.
This study aims to assess the promotional activities of Las Piñas National High School Library based on users' awareness and library usage. The researcher used both qualitative and quantitative analysis and gathered data from 269 respondents through survey questionnaires, interviews and marketing mix analysis
The researcher found out that LPNHS Library has only engaged and implemented promotional activities based on traditional practices they know. It was also mentioned that several problems such as lack of budget, lack of skills and knowledge, lack of staff and government support hinder the library in promoting its services. Most (33.87) of the respondents considered library posters, billboards and slogan as the most effective current promotional tools in the library. However, 33.46 of the respondents revealed that exhibits and displays are their most preferred promotional tools. Generally, most of the users are satisfied in terms of physical facilities, holdings, and collections, reference services and outreach programs
At the end of this study, a promotional plan was designed in relation to the maintenance of the promotional system of LPNHS Library. This is to ensure that promotional activities are guided with appropriate actions and objectives towards the improvement of library services
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Las Piñas National High School Library -- Evaluatio; Public relation -- Libraries -- Philippines -- Las Piñas (Parañaq.